Virulence of Herpes Simplex Virus 1 Harboring a UAG Stop Codon between the First and Second Initiation Codon in the Thymidine Kinase Gene - Nguyen, Phu Hoang Anh; Yamada, Souichi; Harada, Shizuko; Fukushi, Shuetsu; Mizuguchi, Masashi; Saijo, Masayuki (Japanese Journal of Infectious Diseases, 2022)
Herpes simplex virus 1 (HSV-1)-TK (8UAG) expresses a truncated thymidine kinase (TK) translated from the second initiation codon due to a stop codon (UAG) at the 8th position (counted from the first initiation codon). Here, we showed that the sensitivity of HSV-1-TK (8UAG) to acyclovir (ACV) is similar to that of the control HSV-1 wild-type (WT), which expresses an intact TK protein. However, HSV-1-TK (44UAG), which expresses a truncated TK due to a UAG codon at position 44, showed lower sensitivity to ACV. A mouse infection model was used to compare the virulence of HSV-1-TK (8UAG) and HSV-1-TK (44UAG) to that of HSV-1 WT. The 50% lethal dose (LD50) for HSV-1-TK (44UAG) was 7.8-fold higher than that for HSV-1-TK (8UAG), whereas the LD50 for HSV-1-TK (8UAG) was the same as that for the parental HSV-1 WT. There were no statistically significant differences among HSV-1-TK (44UAG), HSV-1-TK (8UAG), and HSV-1 WT with respect to replication capacity and viral TK mRNA expression in the mouse brain. Thus, the virulence of HSV-1 expressing the truncated viral TK translated from the second initiation codon might depend on the position of the UAG stop codon.